The association of liver function biomarkers with internal exposure of short- and medium-chain chlorinated paraffins in residents from Jinan, China. (1st January 2021) - Liu, Yi; Han, Xiumei; Zhao, Nan; Fang, Xinxin; Zhang, Shiwen; Li, Shixue; Jiang, Wei; Ding, Lei
Abstract: Chlorinated paraffins (CPs) are pervasive environmental pollutants which have been reported to be hepatotoxic by laboratory cell and animal studies. However, the related epidemiological reports on their hepatotoxic effects to humans are sparse. In this study, we evaluated the associations between six liver enzymes and serum short-chain CP (SCCP) or medium-chain CP (MCCP) concentrations of 197 residents in Jinan, China. Serum S/MCCPs were detected by quadrupole time-of-flight high-resolution mass spectrometry coupled with atmospheric pressure chemical ionization source (APCI-QTOF-HRMS), and quantified by pattern deconvolution method. The associations between total serum S/MCCP concentrations (ΣS/MCCPs) and continuous liver enzyme levels were assessed by linear regression. Odds ratios (ORs) for the effects of serum ΣS/MCCPs concentrations on liver function biomarkers dichotomized by clinical reference intervals were predicted by logistic regression, either treating ΣS/MCCPs as continuous or categorical dependents. After multivariable adjustment, linear regression results illustrated that 1-ln unit increase in serum ΣSCCPs was negatively associated with male PA levels [-6.08, 95% confidence interval (CI): −11.90, −3.25, p < 0.05], positively associated with male TB levels (1.80, 95% CI: 0.28, 3.31, p < 0.05), and positively associated with female AST levels (1.39, 95% CI: 0.07, 2.70, p < 0.05). One-ln unit increase in serum ΣMCCPs was negatively associated male PA levels (−7.56, 95% CI: −17.15, −4.03, p < 0.05). Logistic regression results suggested that male serum ΣSCCPs were associated with increased prevalence of abnormal PA (OR = 1.47 per 1 ln-unit increase, CI = 1.18, 1.82) and TB (OR = 1.75, 95% CI = 1.12, 2.76) levels, and male serum ΣMCCPs were significantly associated with increased prevalence of abnormal PA (OR = 1.43, 95% CI = 1.03, 1.97) levels. In addition, male participants with concentrations above the median ΣS/MCCPs were associated with increased risk for abnormal PA levels [SCCPs, 2.11-fold (95% CI = 1.15, 3.87); MCCPs, 1.94-fold (95% CI = 1.24, 3.03)]. Male participants with concentrations above the median ΣSCCPs were also associated with increased risk for abnormal TB levels (OR = 1.75, 95% CI = 1.12, 2.76). Conclusively, our results revealed that CP internal exposure was associated with disturbed liver biomarker levels, suggesting the hepatotoxicity of both SCCPs and MCCPs to humans. Graphical abstract: Image 1 Highlights: SCCPs and MCCPs were detected in all (n = 197) serum samples. Liver biomarkers were disturbed by CPs in a sex-dependent way. Serum ΣSCCPs were positively associated with male TB levels and female AST levels. Serum ΣSCCPs and ΣMCCPs were both negatively associated PA levels in males. Our results suggested the hepatotoxicity of both SCCPs and MCCPs. Abstract : Main finding: CP exposure might disturb liver function in terms of liver protein synthesis activity, hepatocytes necrosis and bile ducts problems.